Control of twisted and coiled polymer actuator with anti-windup compensator. (31st May 2018) - Suzuki, Motoya; Kamamichi, Norihiro
Abstract: A twisted and coiled polymer actuator (TCPA) is a novel soft actuator. It is fabricated by twisting nylon thread or fishing line. It can be thermally activated and has remarkable properties such as high power/mass ratio and large deformation. By applying conductive nylon fibers to the actuator, it can be electrically driven by Joule heating. However, if a controller of the actuator is designed without considering an input saturation, the control performance may be descended by windup phenomena. In this paper, to solve this problem, a feedback control with an anti-windup compensator is applied. The validity of the applied method is investigated through numerical simulations and experiments.